Penyelesaian Kasus Kekerasan dalam Rumah Tangga di Desa Andongsari Kecamatan Ambulu Kabupaten Jember - ., Suphia; Kurniasari, Dwi Fefri; Nofitasari, Solehati; Alkahfi Setiawan, Sidi (WELFARE STATE Jurnal Hukum, 2024)
Violence that occurs in the household is a form of physical and emotional abuse which is a way of controlling spouses in household life, so that human values ​​that should be manifested in the family become blurred. This study aims to determine what factors cause cases of domestic violence and how to resolve cases of domestic violence inAndongsari Village, Ambulu District, Jember Regency. In general, the factors that cause domestic violence include economic factors, infidelity factors, socio-cultural factors and the number of children. The factor that caused the occurrence of domestic Violence that occurs in the household is a form of physical and emotional abuse which is a way of controlling spouses in household life, so that human values that should be manifested in the family become blurred. This study aims to determine what factors cause cases of domestic violence and how to resolve cases of domestic violence in Andongsari Village, Ambulu District, Jember Regency. In general, the factors that cause domestic violence include economic factors, infidelity factors, socio-cultural factors and the number of children. The factor that caused the occurrence of domestic violence that occurred in Andongsari Village was triggered by economic problems. Problems related to economic fulfillment are a source of contention between husband and wife. Settlement of cases of domestic violence by asking for help from the closest family to resolve problems between them in deliberation. If these steps fail to resolve the problem, then the victim will report to the Head of the Rukun Tetangga (RT). The role of the village government in an effort to provide protection for survivors of cases of violence against women and children, the Andongsari Village government has formed the Griya Asih Nusa Implementation Team.